Folate and Synthetic Folic Acid Content in Canadian Fortified Foods 20 Years Post Mandatory Fortification (P24-029-19) - Khanna, Siya (Curr Dev Nutr, 2019)
OBJECTIVES: In 1998, Health Canada mandated folic acid fortification of white flour and enriched grain products to reduce the prevalence of neural tube defects. In 2009, we reported that the analyzed folate content of 95 of the mostly commonly purchased folic acid fortified foods in Canada was on average 151 ± 16% of that reported in the Canadian Nutrient File (CNF). The aim of this study was to assess whether 20 years after mandatory fortification, the CNF values for folate and folic acid accurately reflect amounts determined by direct assessment. METHODS: Using the 2007 ACNielsen Company data 15 of the most commonly purchased folic acid-fortified foods from each of the following categories were selected: “breads”, “rolls and buns”, “cookies” and “crackers”. Folate concentrations in foods were determined using the tri-enzyme digestion method followed by a microbiological assay. Synthetic folic acid concentrations were determined using stable-isotope liquid chromatography-mass spectrometry. Analyzed values were compared to the 2015 Canadian Nutrient File; unbranded foods. RESULTS: Our preliminary data show the total folate content analyzed in foods (n = 24 to date) was significantly higher than the CNF values across all categories (P < 0.01) and on average, 187% ± 15 of the CNF values. Similarly, the synthetic folic acid content in foods was significantly higher than CNF values for “rolls and buns” and “cookies” (P < 0.05, P < 0.01 respectively) and on average 163% ± 25 of the CNF values. CONCLUSIONS: These preliminary data suggest, 20 years after mandatory fortification of the food supply, CNF values which include unbranded foods do not accurately represent the amounts of total folate and synthetic folic acid in foods. Hence dietary estimates established using the CNF many significantly underestimate actual intakes due to continued overages in folic acid fortification. FUNDING SOURCES: Natural Sciences and Engineering Research Council of Canada.